PENGARUH ANAK RANDAI TERHADAP PEMASARAN HASIL PERTANIAN SAYURAN (Kasus di Nagari Alahan Panjang Kecamatan Lembah Gumanti) - Yusri, Elda; Arifin, Zainal; Elfemi, Nilda (Pendidikan Sosiologi, 2013)
In agricultural trade vegetables in Nagari Alahan Long Valley District Gumanti require the services of middlemen called randai child. Activities undertaken kids marketing randai affect vegetable crops is in Nagari Alahan Panjang. Randai children directly involved either buy or sell the crop farmers. This study was conducted to see how the influence and child relationship with farmers and toke randai the marketing of vegetable crops is in Nagari Alahan Panjang, especially on the activities carried out by children randai to survive and benefit from his efforts. Based on the above problem definition , the research question is: